2017
DOI: 10.1016/j.jes.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of mesoporous lignin-based biosorbent from rice straw and its application for heavy-metal-ion removal

Abstract: Lignocellulosic biomass offers the most abundant renewable resource in replacing traditional fossil resources. However, it is still a major challenge to directly convert the lignin component into value-added materials. The availability of plentiful hydroxyl groups in lignin macromolecules and its unique three-dimensional structure make it an ideal precursor for mesoporous biosorbents. In this work, we reported an environmentally friendly and economically feasible method for the fabrication of mesoporous lignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…12 Finally, it should be noted that the developed M-ZrP adsorbent exhibits one of the highest maximum adsorption capacity (q max ) of Pb(II) ions reported in literature for a variety of organic, inorganic, hybrid, and MOF adsorbents. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] The removal capacity for lead ions by M-ZrP is 680.4 mg g À1 and 1000 mg g À1 using an adsorbent dose of 1 g L À1 and 2 g L À1 , respectively. This removal capacity is higher than most of the reported values for Pb(II) removal by other ZrP-modied adsorbents such as ZrPchloromethylated polystyrene (556.0 mg g À1 ), 51 polymer based-ZrP (398.0 mg g À1 ), 19 Go-ZrP (363.4 mg g À1 ), 21 ZrP-polysulfone (302.1 mg g À1 ), 52 and ZrP-polyvinyl alcohol (121.1 mg g À1 ).…”
Section: Adsorption Capacity M-zrp For Pb(ii) Hg(ii) and Cd(ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…12 Finally, it should be noted that the developed M-ZrP adsorbent exhibits one of the highest maximum adsorption capacity (q max ) of Pb(II) ions reported in literature for a variety of organic, inorganic, hybrid, and MOF adsorbents. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] The removal capacity for lead ions by M-ZrP is 680.4 mg g À1 and 1000 mg g À1 using an adsorbent dose of 1 g L À1 and 2 g L À1 , respectively. This removal capacity is higher than most of the reported values for Pb(II) removal by other ZrP-modied adsorbents such as ZrPchloromethylated polystyrene (556.0 mg g À1 ), 51 polymer based-ZrP (398.0 mg g À1 ), 19 Go-ZrP (363.4 mg g À1 ), 21 ZrP-polysulfone (302.1 mg g À1 ), 52 and ZrP-polyvinyl alcohol (121.1 mg g À1 ).…”
Section: Adsorption Capacity M-zrp For Pb(ii) Hg(ii) and Cd(ii)mentioning
confidence: 99%
“…59 The q max of M-ZrP is also higher than or comparable to the best graphene-based adsorbents for Pb(II) removal such as chitosan-functionalized GO (556.2 mg g À1 ), 60 GO-wrapped melamine sponge (349.7 mg g À1 ), 61 and 3D-graphene/d-MnO 2 aerogels (643.6 mg g À1 ). 62 Although the sulfur-functionalized porous lignin adsorbent exhibits higher q max (952.0 mg g À1 ) 63 than M-ZrP (680.4 mg g À1 ) at the 1 g L À1 adsorbent dose, this adsorbent requires 300 min to reach this high capacity while the M-ZrP requires only 30 min to achieve the maximum capacity. Moreover, the synthesis of the sulfur-functionalized lignin adsorbent involves complicated modications with long processing time unlike the synthesis of M-ZrP which requires only 2 h under mild reaction conditions.…”
Section: Adsorption Capacity M-zrp For Pb(ii) Hg(ii) and Cd(ii)mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 It is known to possess various functional groups, reactive sites, and high content of guaiacyl, syringyl, and p -hydroxyphenyl chemical units. 2 Various applications of lignin are well recognized, such as an additive to composite materials, 3 antioxidants, 4 adsorbents, 5 sorption of heavy-metal ions, 6 anticancer agents, 7 and dyes. The wide applications of lignin emanate from its substantial amount of functional groups and reactive sites presented in the molecule irrespective of its plant sources.…”
Section: Introductionmentioning
confidence: 99%
“…A small protruding crest at wave number 1420 cm −1 indicated that the compost might contain lignin [41]. Both Marina et al [42] and Xu et al [43] showed that the lignin could adsorb toxic metals. A high protruding peak at the wave number 1030 cm −1 suggested that the compost might contain polysaccharides [41], and Choma et al [44] indicated that polysaccharides were able to adsorb toxic metals.…”
Section: Compost Maturitymentioning
confidence: 98%